Effect of varied soil matric potentials on the iron use efficiency of soybean genotypes (Glycine max L.) - M, Rüştü Karaman (Journal of Research in Biology, 2012)
Bicarbonate has g enerally much more effect on iron chlorosis in soils having excess moisture than in soils having lower moisture. But, soil moisture level may or may not affect the severity of iron deficiency depending on the plant species or genotypes. In this study, a pot experiment was conducted using calcareous soil by growing A-3735, A-3127, SA-88, S-4340, Ilisulu-20 soybean genotypes. Iron fertilizer as FeEDDHA (sequestrene 138, 6% iron) at the levels of 0, 4, 8, 12 μg Fe g-1 was applied to the soil. Pots were irrigated based on increasing soil matric potentials of – 65 kPa (I1), -45 kPa (I2) and -25 kPa (I3), respectively. Chlorophyll contents were measured in fresh leaf samples. After harvest, plant dry matter yield was recorded and total phosphorus, iron, zinc and managnese concentrations in top of soybean plants were determined. Total phosphorus, iron, zinc and manganese contents and accumulations were generally varied among soybean genotypes depending on soil matric potentials. Significant differences were obtained among soybean genotypes for dry weight. Significant correlations ( r = 76, P< 0.01) were also found between iron use efficiency of soybean genotypes and soil matric potentials for different iron levels